The Unraveling Abnormal Resignations of Independent Directors: An Information System Analysis of Influencing Factors and Market Reactions - Wu, Lijia; Dong, Nayan (Edelweiss Applied Science and Technology, 2024)
The governance structures of contemporary organizations face unprecedented challenges arising from financial uncertainties, shifts in ownership structures, increased scrutiny on ethical financial practices, and the growing influence of information systems in decision-making processes. Independent directors, occupying a pivotal role in these governance frameworks, face complex and multifaceted decisions, including the critical choice of resigning from their positions. The main goal of this study is to provide a thorough investigation of the variables impacting independent directors' decisions regarding their resignation. The primary goal of the study is to determine how financial metrics such as Return on Equity and Earnings Management, audit opinions, significant litigation, shifts in the largest shareholder, liquidity ratios, and governance components such information system functioning interact with one another. The study is to add to the body of knowledge on corporate governance theory now available and offer pertinent data for the development of effective organizational governance systems. Conducted as a qualitative study, the research engaged in eight semi-structured interviews, employing a three-step thematic analysis. Through this methodological approach, the research explored the lived experiences of independent directors, unraveling the intricate web of factors influencing their decisions to resign. The findings of the study underscore the significant impact of financial metrics, governance concerns, and the role of information systems on the likelihood of independent director resignations. The interplay between these dimensions reveals a nuanced understanding of the complexities that directors face, emphasizing the need for an integrated approach in examining governance issues. This research contributes original insights by bridging gaps in existing literature and offering a holistic perspective on the factors influencing director resignations. The study's originality lies in its exploration of the interconnected nature of financial, governance, and technological dimensions, providing a nuanced understanding that informs both academic scholarship and practical governance considerations. The significance of this research lies in its potential to guide organizations in fortifying their governance structures, enhancing board effectiveness, and navigating the complexities of the contemporary business environment.